Pengaruh Sistem Pengendalian Internal Terhadap Ketepatan Pelaporan Pajak Bumi Dan Bangunan Pada Badan Pendapatan Kabupaten Bengkalis - Heru Maruta; Ayu Apriliani (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
The purpose of this research was to determine the effect of the internal control system on the accuracy of land and building tax reporting at the Bengkalis Regency Regional Revenue Agency. The populations in this research are employees of the Bengkalis Regency Revenue Agency whose job is to examine the Earth and Building Tax report where the total population is 30 people. The sample in this research used a saturated sample of 30 people. Data collection techniques used were interviews, documentation, questionnaires and literature study. The results of this research are that the internal control system influences the accuracy of land and building tax reporting with a percentage of influence of 62.9%, while the remaining 37.1% is influenced by other variables that are not included in this research model.